Credit Insurance - Jus, Miran (Elsevier Science, 2013)
This monograph is practically oriented, presenting a survey and explanation of credit insurance services for protection of short-term trade receivables primarily against commercial risk of insolvency and protracted default. The subject matter (i.e., main functions, features and principles of credit insurance with detailed description of credit insurance coverage, insurance conditions, and credit insurance policy management) follows procedural stages and presents commercial, financial, legal, and practical points of view which emphasize the needs of both the providers of these services and their clients - existing and potential credit insured companies - as well as other practitioners.